Older Adults’ Needs and Worries about Healthy Living and Mobile Technology: A Focus Group Study - Zaidatol Haslinda Abdullah Sani, Dinna N. Mohd Nizam, Aslina Baharum, Siti Hasanah Tanalol (International Journal of Advanced Science and Technology, 2020)
This paper presents a focus group study among 13 older adults to explore the needs and worries about healthy living and technology usage. Results found that the participants do know how to maintain healthy living. However, they have a lack of knowledge about the amount of daily intake we should consume. They were also found to not prefer to eat alone, and rather not to eat. In related to technology, both positive and negative attitudes were found. However, these participants agreed to have future technology assistants to help them in self-monitoring their healthy lifestyle. Participants suggested having reminders, providing tips, and the ability to view intakes history as the technology assistant’s requirement. They also suggested having ease to use and friendly technology. The implication from this focus group can be useful in the development of healthy living interventions for older adults, which could increase awareness and motivate healthy attitudes and behaviours among them, in particular of eating and drinking healthy.